Genome-wide identification and analysis of terpene synthase (TPS) genes in celery reveals their regulatory roles in terpenoid biosynthesis - Li, Mengyao; Li, Xiaoyan; Zhou, Jin; Sun, Yue; Du, Jiageng; Wang, Zhuo; Luo, Ya; Zhang, Yong; Chen, Qing; Wang, Yan; Lin, Yuanxiu; Zhang, Yunting; et al. (Frontiers in Plant Science, 2022)
Terpenes are an important class of secondary metabolites in celery, that determine its flavor. Terpene synthase (TPS) has been established as a key enzyme in the biosynthesis of terpenes. This study systematically analyzed all members of the TPS gene family of celery (Apium graveolens) based on whole genome data. A total of 39 celery TPS genes were identified, among which TPS-a and TPS-b represented the two largest subfamilies. 77 cis-element types were screened in the promoter regions of AgTPS genes, suggesting the functional diversity of members of this family. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses showed that AgTPS genes were enriched in multiple terpenoid biosynthesis pathways. Transcript abundance analysis and qRT-PCR showed that most AgTPS genes were differentially expressed in different tissues and colors of celery, with AgTPS 6, 9, and 11 expressed differentially in tissues, while AgTPS31, 32, and 38 are expressed differently in colors. More than 70% of the celery volatile compounds identified by HS-SPME-GC/MS were terpene, and the most critical compounds were β-Myrcene, D-Limonene, β-Ocimene and γ-Terpinene. Principal component analysis (PCA) showed that compounds (E)-β-Ocimene, D-Limonene, β-Myrcene and γ-Terpinene predominantly accounted for the variation. Further correlation analysis between gene expression and terpenoid accumulation showed that the four genes AgTPS9, 25, 31 and 38 genes may have positive regulatory effects on the synthesis of D-Limonene and β-Myrcene in celery. Overall, this study identified key candidate genes that regulate the biosynthesis of volatile compounds and provide the foothold for the development and utilization of terpenoids in celery.